Synthesis of Temperature/pH Dual-Responsive Double-Crosslinked Hydrogel on Medical Titanium Alloy Surface - Yutong Li; Jiaqi Wang; Shouxin Liu (Gels)
Medical titanium alloy Ti-6Al-4V (TC4) is widely used as a surgical implant material in biomedical fields owing to its superior biocompatibility, corrosion resistance, and mechanical performance, particularly for osseous integration applications. However, long-term contact of medical titanium-based implants with human soft tissues may induce infection and inflammation. To address these limitations, a drug-loading gel was designed to be synthesized on a TC4 surface to improve biointegration. Considering the critical regulatory roles of temperature and pH in physiological environments, this study synthesized a dual-responsive hydrogel using the temperature-sensitive monomers 2-(2-methoxyethoxy)ethyl methacrylate (MEO2MA) and oligoethylene glycol methacrylate (OEGMA) and the pH-sensitive monomer diethylaminoethyl methacrylate (DEAEMA), employing stereocomplexed polylactic acid as a physical crosslinker and N,N′-methylenebisacrylamide (MBA) as a chemical crosslinker. A polydopamine-based initiator was synthesized via dopamine functionalization with 2-bromoisobutyryl bromide (BIBB). The amphiphilic co-network hydrogel was grafted onto a modified TC4 surface through atom transfer radical polymerization (ATRP). Integration of the drug-loading gel and TC4 gives the implant an “active therapeutic” function by localized drug release. The results demonstrated that the energy storage modulus of the double-crosslinked gel matched that of human soft tissues. The gels exhibited efficient drug release.